Gambaran Penyakit Demam Berdasarkan Umur dan Jenis Kelamin Pasien Rumah Sakit Haji Medan - Henny Yuslina; E. Harso Kardhinata; Sartini sartini (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
The purpose of this research was to determine whether there is a relationship of senile cataract with blood sugar levels for people with diabetes who checked in BKIM (Balai Kesehatan Indera Masyarakat) Medan. Research was done through two stages, blood sampling and examination of blood glucose levels and data analysis. The patient's blood is taken at any time from the patient's fingertip. Data were analyzed calculated the correlation relationship where the cataract as the parameters x and y are the blood sugar levels. Correlation calculation results indicate the number r = 0:46, which means there is less close relationship between cataracts and blood sugar levels but percentages show increased in the percent of patients with both cataracts relation to blood sugar levels as well as cataracts with age. From a study of 60 patients aged 45-65 years who suffer from cataracts are less significant association between cataract with blood sugar levels.